A FIGURATIVE LANGUAGE ANALYSIS OF LYODRA GINTING’S SONG LYRICS IN THE SONG ALBUM ‘LYODRA’ - Lismawati Sarumaha; Fider Putri Hartati Gea; Arsen Nahum Pasaribu (Institut Pendidikan Tapanuli Selatan, 2022)
This article aims to analyze of figurative language in the song lyrics of Lyodra Ginting Album ‘Lyodra’. The writers propose two statements of problem those are; what are figurative languages in the song lyrics of Lyodra Ginting Album ‘Lyodra’, and what is the dominant form of figurative language used In the song lyrics of Lyodra Ginting Album ‘Lyodra’. The writers uses qualitative method in this research. Finally the the writers collected 8 song lyrics from Lyodra Ginting on the album 'Lyodra' and found 7 types of figurative language consisting of Metaphor, Simile, Hyperbole, Personification, Metonymy, Synecdoche, Symbol. The writers found 14 Metaphors, 11 Similes, 10 Hyperboles, 4 Personifications, 2 Metonyms, 1 Synecdoche, 1 Symbol. The kind of figurative language that songwriters use to make each song have deep meaning and come alive. So, using figurative language can lead the reader to the meaning of the lyrics and Metaphor is dominant type that occur in the song lyrics of Lyodra Ginting Album ‘Lyodra’